2015
DOI: 10.1016/j.biocel.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Keap1–Nrf2 signalling in pancreatic cancer

Abstract: a b s t r a c tTranscription factor NF-E2 p45-related factor 2 (Nrf2, also called Nfe2l2), a master regulator of redox homeostasis, and its dominant negative regulator, Kelch-like ECH-associated protein 1 (Keap1), together tightly control the expression of numerous detoxifying and antioxidant genes. Nrf2 and the 'antioxidant response element' (ARE)-driven genes it controls are frequently upregulated in pancreatic cancer and correlate with poor survival. Upregulation of Nrf2 is, at least in part, K-Ras oncogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 131 publications
(211 reference statements)
1
39
0
Order By: Relevance
“…Thus, a dCK-NRF2/ARE feedback loop exists, which collectively renders pancreatic cancer cells gemcitabine resistant we deduced that in addition to the role of dCK in gemcitabine metabolism, this kinase may also contribute to drug resistance by regulating ROS production and the NRF2/ARE axis, which synergistically regulate intrinsic and acquired gemcitabine resistance in pancreatic cancer cells. Previous studies have demonstrated that NRF2 activation is the net result of oncogenic Kras mutation and MAPK pathway activation 29. Consistent with this finding, we also observed a decrease in ERK1/2 activation in dCK-overexpressing PANC-1 and MIA PaCa-2 cells.…”
supporting
confidence: 92%
“…Thus, a dCK-NRF2/ARE feedback loop exists, which collectively renders pancreatic cancer cells gemcitabine resistant we deduced that in addition to the role of dCK in gemcitabine metabolism, this kinase may also contribute to drug resistance by regulating ROS production and the NRF2/ARE axis, which synergistically regulate intrinsic and acquired gemcitabine resistance in pancreatic cancer cells. Previous studies have demonstrated that NRF2 activation is the net result of oncogenic Kras mutation and MAPK pathway activation 29. Consistent with this finding, we also observed a decrease in ERK1/2 activation in dCK-overexpressing PANC-1 and MIA PaCa-2 cells.…”
supporting
confidence: 92%
“…NRF2 and the ARE-driven genes it controls are frequently upregulated in PDAC and correlate with poor survival. Upregulation of NRF2 is, at least in part, Kras-driven and contributes to proliferation and chemoresistance in PDAC (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Temporary activation of NRF2 could protect normal cells from toxins or carcinogens, however, sustained activation of NRF2 will upregulate the expression of downstream genes, thus providing a conducive environment for malignant cells and facilitating cancer progression . Previous research has demonstrated that abnormal activation of NRF2 is associated with lung, breast, bladder, ovarian, pancreatic, and endometrial cancers and liver cancer metastasis . Contrarily, silencing of NRF2 in tumor cells would lead to decreased cell migration and metastasis potential.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Previous research has demonstrated that abnormal activation of NRF2 is associated with lung, breast, bladder, ovarian, pancreatic, and endometrial cancers and liver cancer metastasis. [24][25][26][27][28][29] Contrarily, silencing of NRF2 in tumor cells would lead to decreased cell migration and metastasis potential.…”
Section: Discussionmentioning
confidence: 99%